Characterization and Antimicrobial Activity of Whey Edible Film Composite Enriched with Clove Essential Oil - Fahrullah; Ervandi, M.; Rosyidi, D. (Tropical Animal Science Journal, 2021)
Antimicrobial edible films made from clove essential oil play a role in reducing, inhibiting, or slowing the growth of bacteria that may be existed in food packaging or packaging materials to extend the shelf life of packaged foods. This study aims to produce whey and clove oil films with film thickness, elongation, tensile strength, water vapor transmission rate, optical properties, antimicrobial properties of clove oil, and its inhibition against pathogenic microbes. The physical and antimicrobial characteristics of edible film were investigated using an experimental method in a completely randomized design with four treatments. The treatment used different concentrations of clove oil (C0: 0% clove essential oil, C1: 5% clove essential oil, C2: 10% clove essential oil, and C3: 15% clove essential oil). The percentage value of elongation and microbial inhibitory activity were significantly affected (p